Changes in vegetation coverage with emphasis on the identification of cerrado patches in a topographic profile of the semi-arid region from Pernambuco – Brazil - Santos, Linaldo Severino; Barros Silva, Helena Paula; Pereira, Eugênia Cristina Gonçalves; Silva, Hewerton Alves (Sociedade & Natureza, 2020)
The semi-arid Northeast is one of the least known Brazilian regions in terms of vegetative diversity since claims of there being few plants endemic to the Caatinga are unjustly propagated. However, although this biome has suffered a lot through anthropic action, it presents a great diversity of vegetational types, including disjunctions of other biomes in exceptional areas, such as humid brejos de altitude, which are present as isolated patches in the landscape of the semi-arid Northeast. Thus, in this study, an analysis was made to differentiate the vegetation coverage along a topographic profile, in a spatial transect of the southern Agreste region of Pernambuco, comprising portions of the municipalities of Águas Belas, Iati and Saloá, through 10 plots established along this topographic profile. Application of the Normalized Difference Vegetation Index (NDVI) showed the variation of values as a function of the topography, revealing that in depression areas, where drier caatinga is observed, the lowest value of NDVI was obtained (0.18). On the other hand, in the areas of higher relief, where montane forests and cerrado develop, the highest values were found (0.49), thus showing the influence of topography on the distribution of humidity and vegetational features.